Vertodrom covering calculation and designing technology - Andrii Bieliatynskyi; Oleksandra Akmaldinova; Victoria Akmaldinova (теорія та практика дизайну)
The article is devoted to the analysis of existing methods of calculation of rigid heliport coverings, both domestic and foreign. Considerable attention is paid to the geometric dimensions in the plan and layout; location and orientation of heliports. Types of helipads are considered; materials used in the construction of heliports; type of structures (panels), designed for the construction of helicopter pads at the surface level (on any dense surface or ordinary soil), that successfully replace concrete, as well as for the reconstruction of worn and damaged concrete helicopter pads on rooftops and other heliport modifications; possible locations of helicopter pads, which may be different in size and configuration: mobile, off-road, ground, on the roofs of buildings and structures, on pontoons, on sea or river vessels and yachts, on offshore drilling platforms, by individual projects. Approaches to the improvement of the existing method of calculation and design of rigid helipads are analyzed. A comparative analysis of ICAO, FAA, SNiP 2.05.08-85 regulatory documentation and recommendations, which do not provide a clear idea of ​​the method of calculating the thickness of rigid heliports, do not separate the calculation of heliports from the calculation of aerodrome pavements, do not consider any critical cross sections in calculating the load from helicopters and the main differences in designing coverings for helicopters from those for aircraft maintenance, connected with the dynamics of the takeoff and landing operations. As the weight of modern helicopters varies widely, it has been established that different types of coverings must be used for different weight categories (from structures raised above the ground level for light and medium-weight helicopters to cement concrete coverings for heavy helicopters).